Innovation Learning Geography with ArcGIS Online: The Impact to Skills Collaborative and Achievement Student School Upper Intermediate - Asmororini, Endah; Kinda, Johanis; Şen, Burcu (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: The aim of this research is to examine the influence of ArcGIS online learning media on collaborative skills and student learning outcomes at State Senior High School 1 Mojo, Kediri Regency. Methodology: The research used a quasi-experimental method with a Post-test only control design. The tool used is ArcGIS online from ESRI. The research population was class 10 students at Mojo 1 High School, Kediri, academic year 2023/2024, with samples selected randomly for the experimental and control classes. Data was collected through observation of collaborative skills and post-test for learning outcomes. Observations were carried out with the help of three observers using a collaborative skills observation instrument based on a Likert scale. Data analysis was carried out using SPSS, including the ANOVA test for homogeneity, the Kolmogorov-Smirnov test for normality, and the T test to test significant differences between the experimental and control classes. Main Findings: The use of ArcGIS online as a learning medium shows a significant increase in collaborative skills and student learning achievement compared to conventional learning media. Post-test and observation results show higher scores in the experimental class. Novelty/Originality of this study: This research introduces the use of ArcGIS online as a geography learning medium, which has not been widely implemented in high schools. This study shows that the use of this technology can significantly improve students' collaborative skills and learning outcomes.